Identification of surface processes in individual minerals of a complex ore through the analysis of polished sections using polarization microscopy and x-ray photoelectron spectroscopy (Xps) - Silva-Quiñones, Dhamelyz (2018)
Understanding the changes of a mineral during ore processing is of capital importance for the development of strategies aimed at increasing the efficiency of metal extraction. This task is often difficult due to the variability of the ore in terms of composition, mineralogy and texture. In particular, surface processes such as metal re-adsorption (preg-robbing) on specific minerals are difficult to evaluate, even though they may be of importance as the re-adsorbed material can be blocking the valuable mineral and negatively affect the extraction process. Here, we show a simple yet powerful approach, through which surface processes in individual minerals are identified by combining polarization microscopy (MP) and X-ray photoelectron spectroscopy (XPS). Taking as an example a silver-containing polymetallic sulfide ore from the Peruvian central Andes (pyrite-based with small amounts of galena), we track the changes in the sample during the course of cyanidation. While polarization microscopy is instrumental for identifying mineralogical species, XPS provides evidence of the re-adsorption of lead on a pyrite surface, possibly as lead oxide/hydroxide. The surface of pyrite does not show significant changes after the leaching process according to the microscopic results, although forms of oxidized iron are detected together with the re-adsorption of lead by XPS. Galena, embedded in pyrite, dissolves during cyanide leaching, as evidenced by PM and by the decrease of XPS signals at the positions associated with sulfide and sulfate. At the same time, the rise of a lead peak at a different position confirms that the re-adsorbed lead species cannot be sulfides or sulfates. Interestingly, lead is not detected on covellite surfaces during leaching, which shows that lead re-adsorption is a process that depends on the nature of the mineral. The methodology shown here is a tool of significant importance for understanding complex surface processes affecting various minerals during metal extraction.